Study of possible intrauterine infection of goat fetus with caprine arthritis-encephalitis virus - V. Yu. Koptev; N. A. Shkil; N. Yu. Balybina; T. N. Belenkova (Ветеринария сегодня)
Caprine arthritis-encephalitis is a serious challenge for the modern goat breeding both in Russia and abroad. The disease is quite widespread in our country, causing serious economic damage to the backyard and family-operated farm owners. The etiologic agent of caprine arthritis-encephalitis (CAE) is a virus of the Retroviridae family, which is part of the group of small ruminant lentiviruses subdivided into five genetic groups. A number of reasons prevent timely disease diagnosis, for example, lack of a legal framework regulating preventive measures, prolonged asymptomatic virus-carrier state, and absence of pathognomonic symptoms. There are two routes of the CAE virus spread: vertical (lactogenic), when colostrum or milk from a seropositive goat serves as a transmission factor; and horizontal – from a diseased animal to a healthy one in case of crowded housing, feeding from common drinkers and feeders, as well as during mating. The published data on the possibility of the intrauterine virus transmission from mother to fetus are diametrically different. The purpose of this study was to explore the possibility of intrauterine infection with the CAE virus. Pregnant goats with ELISAand PCR-confirmed CAE diagnosis were used in the study. Pathological material was collected from newborn goats obtained by sterile kidding, and the samples were PCR tested for the CAE causative agent. None of the tested samples demonstrated CAE that gives evidence of absence of the fact of intrauterine virus transmission from the diseased mother to the fetus. Results of long-term monitoring of the goat population kept on two backyards located in the Southern Federal District and Novosibirsk Oblast comprise an indirect evidence of that. The owners of these backyards, where 100% of the goat population were infected with CAE virus, decided to carry out a complex of the disease control measures. Sterile kidding followed by kids’feeding with colostrum and milk pasteurized at 60 °C for 30 minutes with the subsequent use of a whole milk substitute allowed to obtain a CAE-free herd in two years avoiding any significant economic losses and purchase of healthy animals from other farms.